AKIBAT HUKUM BERAKHIRNYA HUBUNGAN KERJA PADA PERUSAHAAN YANG DINYATAKAN PAILIT - Wulandari, Ely Kristina; Markeling, I Ketut; Dedy Priyanto, I Made (Kertha Semaya : Journal Ilmu Hukum, 2013)
Bankruptcy of a company is impact on the working relationship between workers and employers. Legal consequences arising after the company cut off bankruptcy should be known by each party in the company, both the workers and the employers. So that when the company actually experienced bankruptc, neither party feels aggrieved and prepare for the possibility of it.
Keywords: Legal Consequences, Working Relationship, Bankruptcy